Polyacrylonitrile/polyvinyl alcohol-based porous carbon nanofiber electrodes for supercapacitor applications - Altın, Yasin; Bedeloğlu, Ayşe (John Wiley and Sons Ltd, 2021)
Porous carbon nanofibers (PCNFs) were produced from polyacrylonitrile (PAN)/polyvinyl alcohol (PVA) hybrid nanofibers with different mixing ratios and used as the free-standing, flexible, high performance electrodes for the supercapacitors. The effect of PAN/PVA ratio, PVA removing and stabilization/carbonization process on the chemical structure, and the morphology of PAN/PVA hybrid nanofibers and PCNF were investigated by Fourier transform infrared (FT-IR), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analyzer (TGA). It was proved by FT-IR and FE-SEM analyses that PAN/PVA hybrid nanofibers are successfully produced and carbonized. In addition, the electrochemical performance of PCNF electrodes was analyzed by cyclic voltammetry (CV), galvanostatic charge/discharge (GCD), and electrochemical impedance spectroscopy (EIS) methods. Results showed that PCNFs exhibit higher specific capacitance and better electrochemical performance than neat carbon nanofibers (N-CNF). The specific capacitance of the EK5 PCNF (67/33 PAN/PVA wt ratio) was 157 F/g at 5 mV/s scan rate in 1 M H2SO4, while the specific capacitance of N-CNF was 96 F/g at the same conditions. Moreover, the PCNF showed excellent cyclic stability without losing performance through 2500 charge/discharge cycles at a current density of 2 A/g. As a result, free-standing, flexible, and high-performance PCNFs are excellent candidates as supercapacitor electrodes for flexible energy-storage devices.
Keywords: cyclic voltammetry; electrospinning; hybrid nanofiber; porous carbon nanofiber; supercapacitor